PERDAMAIAN YANG TERCAPAI DALAM KEPAILITAN YANG BERASAL DARI PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) (Studi Putusan No. 59/Pdt.Sus-PKPU/2019/PN.Niaga.Sby) - Horman Siregar (Collegium Studiosum Journal, 2023)
Law No. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU) only prohibits debtors from submitting a reconciliation plan if declared bankrupt based on Article 285, Article 286 and Article 292. This research seeks to answer legal issues regarding the legal position of debtors and creditors in bankruptcy after the plan has been rejected. peace in the PKPU process. To answer the research problem, this study uses a type of normative legal research with a statutory approach, a conceptual approach, and a case approach in the form of a Surabaya Commercial Court decision which has permanent legal force. The data used are secondary data in the form of primary, secondary and tertiary materials, obtained through library research or document studies. The results of this study indicate that debtors and creditors can still reach peace even though the Commercial Court has declared the debtor in a state of bankruptcy originating from PKPU. The legal considerations of the panel of judges in ratifying the reconciliation of PT Anugrah Kembang Sawit Sejahtera in bankruptcy originating from PKPU as stated in Decision No. 59/Pdt.Sus-PKPU/2019/PN.Niaga.Sby at the Commercial Court at the Surabaya District Court is the result of voting for a bankruptcy debtor's settlement proposal that has been approved by the creditor in accordance with the provisions of Article 151 of the Bankruptcy Law and PKPU which is then set forth in a peace agreement. In addition, the Court did not find any reasons for refusing to ratify the settlement in accordance with Article 159 paragraph (2) of Law No. 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Payment of Debt, the court is obliged to give a decision regarding the ratification of the settlement.